Self-managed physical activity in cancer survivors for the management of cancer-related fatigue: A scoping review. - Isabella Campanini; Maria Bernadette Ligabue; Maria Chiara Bò; Maria Chiara Bassi; Mirco Lusuardi; Andrea Merlo (PLoS ONE)
Objective Cancer-related fatigue (CRF) is a disabling chronic condition that cancer survivors could experience during and after recovery and that might benefit from self-managed physical activity (PA) programs. This scoping review aimed to map self-managed PA interventions found in literature for the management of CRF. Methods Given the heterogeneity of the topic, scoping review methodological frameworks were used. Pubmed, Cinahl and Cochrane databases were searched for primary literature. Inclusion criteria: self-managed PA meant as any exercise program prescribed by a professional either with or without initial supervision and training which then continued independently for a given time frame; patient-reported fatigue assessment included in the outcome measures. Articles dealing with entirely supervised interventions, dietary or psychological-only therapies, and with palliative care were excluded. Results Of the 543 experimental or observational studies screened, 63 were included. Of these forty-three studies were randomized controlled trials. Data were summarized in tables describing self-managed interventions according to: type of self-managed activity, frequency and duration, strategies to promote adherence, professionals supervising the treatment, outcome measures, and efficacy. A narrative synthesis was also added to further explain findings. Conclusions We collected the available evidence on PA when this was self-managed by patients after prescription by a healthcare provider. Clinicians and researchers should consider incorporating self-care programs in CRF patients' recovery journey gradually, identifying the best strategies to integrate them into daily life. Researchers should specify the characteristics of PA programs when designing new studies. This review highlighted the areas to be investigated for future studies pertaining to self-managed PA.